Exploring the Effects of Mitonuclear Interactions on Mitochondrial DNA Gene Expression in Humans - Torres-Gonzalez, Edmundo; Makova, Kateryna D. (Frontiers in Genetics, 2022)
Most mitochondrial protein complexes include both nuclear and mitochondrial gene products, which coevolved to work together. This coevolution can be disrupted due to disparity in genetic ancestry between the nuclear and mitochondrial genomes in recently admixed populations. Such mitonuclear DNA discordance might result in phenotypic effects. Several nuclear-encoded proteins regulate expression of mitochondrial DNA (mtDNA) genes. We hypothesized that mitonuclear DNA discordance affects expression of genes encoded by mtDNA. To test this, we utilized the data from the GTEx project, which contains expression levels for ~100 African Americans and >600 European Americans. The varying proportion of African and European ancestry in recently admixed African Americans provides a range of mitonuclear discordance values, which can be correlated with mtDNA gene expression levels (adjusted for age and ischemic time). In contrast, European Americans did not undergo recent admixture. We demonstrated that, for most mtDNA protein-coding genes, expression levels in energetically-demanding tissues were lower in African Americans than in European Americans. Furthermore, gene expression levels were lower in individuals with higher mitonuclear discordance, independent of population. Moreover, we found a negative correlation between mtDNA gene expression and mitonuclear discordance. In African Americans, the average value of African ancestry was higher for nuclear-encoded mitochondrial than non-mitochondrial genes, facilitating a match in ancestry with the mtDNA and more optimal interactions. These results represent an example of a phenotypic effect of mitonuclear discordance on human admixed populations, and have potential biomedical applications.